Improving genome assemblies by sequencing PCR products with PacBio - Xiaojing Zhang; Karen W. Davenport; Wei Gu; Hajnalka E. Daligault; A. Christine Munk; Hazuki Tashima; Krista Reitenga; Lance D. Green; Cliff S. Han (BioTechniques)
Advances in sequencing technologies have dramatically reduced costs in producing high-quality draft genomes. However, there are still many contigs and possible misassembled regions in those draft genomes. Improving the quality of these genomes requires an efficient and economical means to close gaps and resequence some regions. Sequencing pooled gap region PCR products with Pacific Biosciences (PacBio) provides a significantly less expensive means for this need. We have developed a genome improvement pipeline with this strategy after decreasing a loading bias against larger PCR products in the PacBio process. Compared with Sanger technology, this approach is not only cost-effective but also can close gaps greater than 2.5 kb in a single round of reactions, and sequence through high GC regions as well as difficult secondary structures such as small hairpin loops.